A System for Improving the Reproductive Culture of Future Primary School Teachers - Kenjaboeva Nigora Mamayusufovna (International Journal of Advanced Science and Technology, 2020)
Extensive work has been carried out around the world to support research aimed at improving reproductive health, the introduction of modern methods and technologies, as well as improving the medical knowledge and culture of young people. The United Nations Population Fund (UNFPA) Millennium Development Goals (MDGs) Action Plan for Healthy Lifestyles, the World Health Organization (WHO) “WHA57.12 Reproductive Health: International Development Goals and Acceleration Achievements Special attention is paid to